2018
DOI: 10.12659/msm.907514
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mTORC1/2 Complexes Inhibit Tumorigenesis and Enhance Sensitivity to 5-Flourouracil (5-FU) in Hepatocellular Carcinoma: A Preclinical Study of mTORC1/2-Targeted Therapy in Hepatocellular Carcinoma (HCC)

Abstract: BackgroundAlthough 5-Flourouracil(5-FU) is used as the first-choice treatment for advanced hepatocellular carcinoma (HCC), it is associated with acquired and intrinsic resistance. Hyperactivation of mTOR signaling has been linked to tumorigenesis and chemoresistance in HCC. The aim of this study was to evaluate and compare the antitumor effects of mTORC1 inhibitor everolimus and mTORC1/2 inhibitor AZD8055 and to examine the interaction between 5-FU and mTORC1/2 inhibitor in HCC.Material/MethodsUsing cultured H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Additionally, using tissues and cells from patients with papillary thyroid cancer, an altered overexpression of glutaminase was observed. When GLS was inhibited using a siRNA, mTORC1-signaling pathway was deactivated leading to an increase of autophagy and apoptosis (160).…”
Section: Glutaminolysis and Mtorc1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, using tissues and cells from patients with papillary thyroid cancer, an altered overexpression of glutaminase was observed. When GLS was inhibited using a siRNA, mTORC1-signaling pathway was deactivated leading to an increase of autophagy and apoptosis (160).…”
Section: Glutaminolysis and Mtorc1 In Cancermentioning
confidence: 99%
“…Rapamycin is the first known allosteric mTORC1 inhibitor studied, however, its poor water solubility and chemical stability have led to implement instead the use of semi-synthetic rapamycin analogs (or rapalogs) that show improved pharmacokinetic properties, solubility and reduced immunosuppressive effects (159,160). To date, three rapalogs are being tested in clinical trials, CCI-779 (temsirolimus), AP23573 or MK-8669 (ridaforolimus), and RAD001 (everolimus) (198).…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%
“…Currently, some studies have reported that TSC2 could be a therapeutic target in HCC. 9–11 However, the value of TSC2 in predicting the prognosis after hepatectomy was rarely reported. In this study, we aimed to detect the genomic variations (GAs) of HCC and evaluated the potential value of TSC2 in predicting the prognosis of HCC patients after hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hepatocarcinogenesis is associated with multiple etiological factors, such as alcohol abuse, epigenetic alterations, hepatitis cirrhosis, and virus infection. [2][3][4] Till now, surgical resection and liver transplantation are still the preferred and effective therapies for early stage of HCC patients, but the recurrence rate is >65%. 5,6 In addition, most patients are diagnosed at advanced stage that vitiates the therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%